VNIIFK - Golovnoe uchrezhdenie otechestvennoi sportivnoi nauki - Fomin, Yu. A.; Smelovskaya, Z. K. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
This paper is devoted to the 65-th anniversary of the oldest Russian research institution of the sports science All-Russian Research Institute of Physical Culture in Moscow. The author describes the history of that scientific institution`s development, the structure of its scientific activities` directions, the role of the institutes specialists in the development of the soviet and Russian sport science and their contribution into the successes of the sport for all, the elite sport and the Olympic movement in Russia and in the USSR.